2019
DOI: 10.1108/prt-06-2019-0052
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon prepared from pistachio waste for dye adsorption: experimental and CCD-based design

Abstract: Purpose This study aims to activated carbon prepared from pistachio waste by using phosphoric acid as chemical activator agent. Activated carbon adsorbents were prepared from pistachio waste by using phosphoric acid as chemical activator agent. Design/methodology/approach The optimum conditions for the highest adsorption performance were determined by central composite design (CCD). The adsorbent was used for the adsorption of dye reactive black 5 (RB5), and the parameters affecting the adsorption were discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Another study found that the annual dry biomass available for energy production in southern Italy was 1.493 tonne/ha [72]. In contrast, another study in Iran reported that the total pistachio waste available for bio-oil production was 1.73 tonne/ha [73].…”
Section: Accessible Crop Residuesmentioning
confidence: 96%
“…Another study found that the annual dry biomass available for energy production in southern Italy was 1.493 tonne/ha [72]. In contrast, another study in Iran reported that the total pistachio waste available for bio-oil production was 1.73 tonne/ha [73].…”
Section: Accessible Crop Residuesmentioning
confidence: 96%
“…1.3.1.1 pH. pH is the most critical parameter affected by heavy metals adsorption efficiency (Dalvand et al, 2016;Mehralian et al, 2020). The pH effect is related to changes in the surface properties of nanocomposites, species distribution of the target metal ions and the ionization degree of adsorptive ions; therefore, the solution pH is a significant parameter affecting the capacity of nanocomposite in water treatment (Zhang et al, 2016;Betiha et al, 2020).…”
Section: Effect Of Different Parameters On Pb 21 Adsorptionmentioning
confidence: 99%
“…33 Langmuir isotherm defines adsorption by a single-layer homogeneous adsorption on surface while Freundlich isotherm assumes a multilayer heterogeneous adsorption present on the surface. 6,34 The calculated adsorption parameters were given in Table 1. For cellulose-based adsorbent, Freundlich isotherm with a R 2 value of 0.949 fits the experimental data better than Langmuir isotherm.…”
Section: Adsorption Isotherms Of Cellulose-based Adsorbentmentioning
confidence: 99%